A high performance hybrid parallel algorithm for fast calculation of 3-D convolution/correlation using the 3-D VR FHT for multi-dimensional signal processing applications. (29th September 2005) - Boussakta, Said; Aziz, Mohamed
In this paper, a fast and efficient 3-D digital filtering method based on the combination of a 3-D hybrid parallel filtering algorithm and the 3-D vector radix fast Hartley transform (3-D VR FHT) is presented. This algorithm is suitable for high resolution/high speed multi-dimensional signal and image processing. The 3-D hybrid parallel algorithm is highly parallel and efficient, as it overcomes the computations overhead and performance limitations associated with the block filtering method by eliminating the overlapping blocks and boundary conditions in parallel filtering applications. It also lifts the restrictions on the input size for high performance, as both the 3-D input data and impulse response of the system are segmented into smaller sub-sections. These sub-sections are independent and can be simultaneously processed. The algorithm's structure and mathematical derivation are given and the performance of the algorithm is tested and presented using a real multi-processor parallel system with 4-DSPs.